Does availability of resources influence grazing strategies in female Svalbard reindeer? - Snorre Henriksen; Ronny Aanes; Bernt-Erik Sæther; Thor Harald Ringsby; Jarle Tufto (Rangifer, 2003)
Foraging strategies and range use in wild female Svalbard reindeer (Rangifer tarandus platyrhynchus) were studied in two areas where the historical grazing pressure differed. We mapped vegetation where the reindeer were seen grazing, and related forage availability to characteristics such as home range size, activity budgets and reproductive status. There were significant differences in quantity of forage available between the two areas and the utilization of vegetation types differed between the sites. However, we found no difference in home range size between the two sites, and individual home range sizes were not related to forage quantity, possibly a result of a skewed and small sample size. Even though significant differences in availability of plant species and groups were found, no variation in home range size was found between reproductive and non-reproductive females on Brøggerhalvøya. Neither did we find any differences between areas or between reproductive groups within or between areas in how female reindeer allocated use of time, or in number of steps taken. However, a significant three way interaction indicated that some variance existed between reproductive groups within or between areas, but we do not conclude that this indicate different grazing strategies. Thus, even though variation in the duration of previous grazing has evidently resulted in rather different foraging conditions in our two areas, we detected no differences in present-day foraging behaviour. Thus, our analyses suggest no relationship or feedback between past grazing and current foraging behaviour in these reindeer.